The bacterial SRP receptor, SecA and the ribosome use overlapping binding sites on the SecY translocon - Kuhn, Patrick; Weiche, Benjamin; Sturm, Lukas; Sommer, Erik; Drepper, Friedel; Warscheid, Bettina; Sourjik, Victor; Koch, Hans-Georg (Traffic, 2011)
Signal recognition particle (SRP)-dependent protein targeting is a universally conserved process that delivers proteins to the bacterial cytoplasmic membrane or to the endoplasmic reticulum membrane in eukaryotes. Crucial during targeting is the transfer of the ribosome-nascent chain complex (RNC) from SRP to the Sec translocon. In eukaryotes, this step is co-ordinated by the SRβ subunit of the SRP receptor (SR), which probably senses a vacant translocon by direct interaction with the translocon. Bacteria lack the SRβ subunit and how they co-ordinate RNC transfer is unknown. By site-directed cross-linking and fluorescence resonance energy transfer (FRET) analyses, we show that FtsY, the bacterial SRα homologue, binds to the exposed C4/C5 loops of SecY, the central component of the bacterial Sec translocon. The same loops serve also as binding sites for SecA and the ribosome. The FtsY-SecY interaction involves at least the A domain of FtsY, which attributes an important function to this so far ill-defined domain. Binding of FtsY to SecY residues, which are also used by SecA and the ribosome, probably allows FtsY to sense an available translocon and to align the incoming SRP-RNC with the protein conducting channel. Thus, the Escherichia coli FtsY encompasses the functions of both the eukaryotic SRα and SRβ subunits in one single protein.
Gesehen am 11.07.2022